The watcher - Howe, James, 1946- (New York : Aladdin Paperback, 1997)
As she sits watching a seemingly perfect family and a handsome lifeguard on the beach, a lonely, troubled girl projects herself into the fantasy lives she has created for them.
Keywords: Family problems -- Fiction; Child abuse -- Fiction; Beaches -- Fiction